An Optimistic Outlook Creates a Rosy Past: The Impact of Episodic Simulation on Subsequent Memory. (June 2018) - Devitt, Aleea L.; Schacter, Daniel L.
People frequently engage in future thinking in everyday life, but it is unknown how simulating an event in advance changes how that event is remembered once it takes place. To initiate study of this important topic, we conducted two experiments in which participants simulated emotional events before learning the hypothetical outcome of each event via narratives. Memory was assessed for emotional details contained in those narratives. Positive simulation resulted in a liberal response bias for positive information and a conservative bias for negative information. Events preceded by positive simulation were considered more favorably in retrospect. In contrast, negative simulation had no impact on subsequent memory. Results were similar across an immediate and delayed memory test and for past and future simulation. These results provide novel insights into the cognitive consequences of episodic future simulation and build on the optimism-bias literature by showing that adopting a favorable outlook results in a rosy memory.